If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 18 + -3(x + -1) = 8x + -1(7x + -9) + 6x + 6 Reorder the terms: -5x + 18 + -3(-1 + x) = 8x + -1(7x + -9) + 6x + 6 -5x + 18 + (-1 * -3 + x * -3) = 8x + -1(7x + -9) + 6x + 6 -5x + 18 + (3 + -3x) = 8x + -1(7x + -9) + 6x + 6 Reorder the terms: 18 + 3 + -5x + -3x = 8x + -1(7x + -9) + 6x + 6 Combine like terms: 18 + 3 = 21 21 + -5x + -3x = 8x + -1(7x + -9) + 6x + 6 Combine like terms: -5x + -3x = -8x 21 + -8x = 8x + -1(7x + -9) + 6x + 6 Reorder the terms: 21 + -8x = 8x + -1(-9 + 7x) + 6x + 6 21 + -8x = 8x + (-9 * -1 + 7x * -1) + 6x + 6 21 + -8x = 8x + (9 + -7x) + 6x + 6 Reorder the terms: 21 + -8x = 9 + 6 + 8x + -7x + 6x Combine like terms: 9 + 6 = 15 21 + -8x = 15 + 8x + -7x + 6x Combine like terms: 8x + -7x = 1x 21 + -8x = 15 + 1x + 6x Combine like terms: 1x + 6x = 7x 21 + -8x = 15 + 7x Solving 21 + -8x = 15 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 21 + -8x + -7x = 15 + 7x + -7x Combine like terms: -8x + -7x = -15x 21 + -15x = 15 + 7x + -7x Combine like terms: 7x + -7x = 0 21 + -15x = 15 + 0 21 + -15x = 15 Add '-21' to each side of the equation. 21 + -21 + -15x = 15 + -21 Combine like terms: 21 + -21 = 0 0 + -15x = 15 + -21 -15x = 15 + -21 Combine like terms: 15 + -21 = -6 -15x = -6 Divide each side by '-15'. x = 0.4 Simplifying x = 0.4
| V(x)=33x+162findx | | 12z+17=11z | | C=38.17+0.50 | | 2z^8/7z^7 | | v=144(3.14) | | 4(w-13)+17=19 | | -9x-5(3-4x)=6(x-4)-36 | | -7(x+4)= | | X=-(-10)/2(-5) | | 6h-h+2=17 | | 3x+7(x-9)=3(x-14) | | 6x+7=7x-1 | | Sin=-2 | | 14-w=17 | | cosz=-2 | | -1/2=3/5y-1/3 | | 9(3a+8)= | | cosz=-3 | | 4x^4/6/5x^3/6 | | -1/3v-1/2=-3/7 | | 12+2j=-j | | 5X=245 | | Y=-4x^2+16x-16 | | (4x+25)+x=180 | | 20+2k=-18k | | 5x+6=30+3x | | 5p^2+3=12p | | 3x^2+9x=-30 | | 5x/3+15/2=2x+10 | | -3(c+3)=4(c+3) | | 11-k=-10 | | 2(c-14)=-8 |